Cell attachment and spreading on metal implant materials - Schwartz, J; Avaltroni, M; Danahy, M; Silverman, B; Hanson, E; Schwarzbauer, J; Midwood, K; Gawalt, E (2003)
Strong bonding and coverage of organic siloxanes or phosphonates on both Ti and Ti-Al-4V can be obtained using either of two novel metal-organic interfaces. Surface coverages are considerably higher than can be effected by direct silanization of the native oxide surfaces. Furthermore, these interfaces can be used to attach the fibronectin attachment peptide arginine-glycine-aspartic acid (RGD) to Ti-6Al-4V. Essentially, no osteoblast adhesion occurred on unmodified Ti-6Al-4V or on alkyl, ω-hydroxy, ω-carboxylic acid, or ω-carboxylateterminated alkylphosphonate-modified surfaces. Adhesion and spreading of osteoblasts on RGD-modified surfaces was quite substantial. © 2002 Elsevier Science B.V. All rights reserved.